Evaluation of the Structural, Biological, and Bone Induction Properties of Sol–Gel–Derived Lithium‐Doped 68S Bioactive Glass—An in Vitro Study on Human Dental Pulp Stem Cells - Pejman Janbaz; Faeze Behzadpour; Kiana Ghanadan (Clinical and Experimental Dental Research, 2025)
ABSTRACT Objectives Calcium silicate–based bioactive glass shows enhanced ion release capabilities and promotes the formation of hydroxyapatite (HA). This study aimed to synthesize a sol–gel–derived 68S bioactive glass (BAG) incorporating lithium (Li) and evaluate its structural, biological, and osteoinductive properties using human dental pulp stem cells (hDPSCs). Materials and Methods Two types of 68S BAG were synthesized using the sol–gel method: one containing 5 mol.% lithium nitrate (BGLi5) and a lithium‐free control (BG). Structural characterization and HA formation were assessed using field emission scanning electron microscopy (FESEM) and Fourier‐transform infrared spectroscopy (FTIR) before and after immersion in simulated body fluid (SBF) on Days 1, 3, and 7. The dissolution rates of the specimens were evaluated using inductively coupled plasma atomic emission spectroscopy (ICP‐AES) and pH analysis. Biological activities were investigated through cell viability (MTT assay), alkaline phosphatase (ALP) enzyme activity, and alizarin red staining to assess mineralization. Additionally, the antimicrobial efficacy of the materials was tested against Streptococcus mutans (SM). Results FTIR and FESEM analyses confirmed the formation of HA crystals in BGLi5 specimens by Day 3 and in BG specimens by Day 7. The MTT assay demonstrated enhanced cell viability in both BG and BGLi5 compared to the control group. ALP activity, a marker of cell differentiation, was significantly elevated in the BGLi5‐DM group by Day 14. Alizarin red staining on Day 21 revealed a marked increase in mineralization in both BG and BGLi5, with the BGLi5‐DM group showing the highest mineralization levels. Furthermore, both BG and BGLi5 demonstrated significant antimicrobial activity against SM. Conclusion The sol–gel–derived 68S BAG containing 5 mol.% Li is a biocompatible material that enhances cell proliferation, differentiation, and mineralization. The combination of BGLi5 with differentiation‐specific culture medium synergistically promotes osteogenic differentiation and mineralization, making it a promising candidate for dental and bone tissue engineering applications.